0160 Development of an instrument assessing symptom exaggeration in patients receiving disability benefits secondary to mental health disorders. (23rd June 2014) - Ebrahim, Shanil; Bance, Sheena; Montoya, Luis; Mulla, Sohail; el Din, Mostafa Kamal; Malachowski, Cindy; Guyatt, Gordon; Busse, Jason
Abstract : Objectives: Symptom exaggeration is a significant issue in patients receiving disability benefits secondary to mental health disorders. Measures designed to detect exaggeration of symptoms are valuable for informing more accurate diagnoses, which can impact claim decision-making, both for disability claim approval and patient management. Our objectives were: 1) to complete a systematic review to identify measures that assess symptom exaggeration in mental health disorders, and 2) using the results from the review, develop an instrument assessing symptom exaggeration in individuals receiving disability benefits secondary to mental health disorders. Method: We completed searches of MEDLINE and PSYCInfo from inception of each database to June 2013, to identify primary studies evaluating symptom exaggeration among patients with mental health disorders. Teams of reviewers completed title and abstract screening of citations, full text review of potentially eligible articles, data extraction, and quality assessment of eligible studies. Findings from our review and input from content experts informed the development of a summary instrument. Results: We identified 8435 unique citations; 102 studies were eligible. Studies reported on 55 different instruments to assess symptom exaggeration; 42% of studies used the MMPI-2. Quality of studies ranged from low to moderate. Items that comprise our summary instrument will be presented at EPICOH. Conclusions: Multiple instruments are available to assess symptom exaggeration among patients presenting with mental illness; however, no instrument has shown ideal psychometric properties. We are hopeful that our instrument will facilitate the testing and development of a novel tool with superior sensitivity and specificity for detecting symptom exaggeration.